To solve the system of equations using the substitution method, we have:
- \( y = -3 \)
- \( y = 2x + 1 \)
Since the first equation gives us a value for \( y \), we can substitute this value into the second equation.
Substituting \( y = -3 \) into the second equation:
\[ -3 = 2x + 1 \]
Now, we need to solve for \( x \):
- Subtract \( 1 \) from both sides:
\[ -3 - 1 = 2x \] \[ -4 = 2x \]
- Divide both sides by \( 2 \):
\[ x = -2 \]
Now that we have \( x = -2 \), we can substitute this back into the first equation to find \( y \):
\[ y = -3 \]
So the solution of the system of equations is:
\[ (x, y) = (-2, -3) \]
In coordinate form, the solution is:
\[ (-2, -3) \]